iNAP: An agricultural portal for the province of Ilocos Norte, Philippines - Villacillo, Reynold Peneyra (Animo Repository, 2008)
The use of the Internet provides new opportunities. These opportunities bring changes and transformations in the way people live. People in all fields embrace these challenges. The field of agriculture, being the cornerstone of the Philippine economy as it braces itself to global frontier, is harnessing the Internet to bring about changes and developments in rice-based farming activities. iNAP, an agricultural portal for the province of Ilocos Norte, Philippines, holds to the promise of the Internet. It is developed to bring about changes to the agricultural communities of the province by empowering them with need-to-know information and knowledge for better farming activities, initiatives, and programs on-the-fly. It also provides a facility for better sharing of experiences, practices, and observations through the use of Internet based forum and messaging. The iNAP web portal is mainly used by the Office of the Provincial Agriculture of Ilocos Norte and its 23 Municipal Agricultural Offices. The main features of the portal include information dissemination, sharing of information, and establishing interaction among agriculture stakeholders in the province. iNAP as a web portal offers functionalities for viewing, searching, downloading, messaging, printing, and updating information as well as submission of critical reports online. The web portal builds on effort to enhance better delivery of public services to the agriculture communities in the province. iNAP, as a forebear of better information dissemination, empowers communities and transforms the activities of the agriculture stakeholders of Ilocos Norte.